Application of the Modified Basic Life Support Training Model in Improving Community Residents’ Rescue Willingness in Nantong City in China - Yu-Fei Qian; Yu-Qin Ren; Li Wang; Rong-Qian Sun; Dan-Feng Li (International Journal of Clinical Practice)
Objective. This study explores the application and effect of the modified basic life support training in improving the first-aid level and rescue willingness of community residents in China. Methods. A total of 94 residents of a community in Nantong city were selected as the subjects by cluster sampling to receive the modified basic life support (BLS) training. The BLS knowledge, attitudes, and behaviors of all recruited subjects were evaluated by a questionnaire before and after training. A skill operation assessment was used to evaluate the effectiveness of the modified BLS training. Results. There were statistically significant differences in the BLS rescue willingness, theory, and skill scores before and after the training P<0.01. A total of 93.62% of the residents considered the modified BLS training model easier to learn and acceptable than the traditional model, and 92.55% of them thought the training content and teaching arrangement were reasonable. Conclusion. The modified BLS training model could improve the community residents’ rescue willingness and skill mastery rates, enhance their first-aid skills and awareness, reduce the risk of disease transmission to a certain extent, and improve the success rate of prehospital first aid to ensure the safety of rescuers and patients.